The Role of Atropine in Preventing Myopia Progression: An Update - Alberto Chierigo; Lorenzo Ferro Desideri; Carlo Enrico Traverso; Aldo Vagge (MDPI AG, 2022)
Several approaches have been investigated for preventing myopia progression in children and teenagers. Among them, topical atropine has shown promising results and it is being adopted in clinical practice more and more frequently. However, the optimal formulation and treatment algorithm are still to be determined. We discuss the pharmacokinetic, pharmacodynamic, clinical, and tolerability profile revealed first by the multicenter, randomized ATOM 1 and 2 trials and, more recently, by the LAMP Study. Results from these trials confirmed the efficacy of low-concentration atropine with a concentration-dependent response. Although atropine at 0.025% and 0.05% concentrations has shown the most encouraging results in large-scale studies, these formulations are not yet commonplace in worldwide clinical practice. Moreover, their rebound effect and the possibility of reaching a stabilization effect have not been fully investigated with real-life studies. Thus, further larger-scale studies should better characterize the clinical efficacy of atropine over longer follow-up periods, in order to define the optimal dosage and treatment regimen.